PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS IV SDN 005 GUNUNG SARI - Susilawati; Rizki Ananda; Kasman Edi Putra (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the increase in teacher activity, student activity, and students' understanding of concepts through the Contextual Teaching and Learning (CTL) approach at SDN 005 Gunung Sari. This research uses Classroom Action Research (CAR) and is carried out in class IV-1 with a total of 34 students. Based on the results of data analysis of the teacher activity observation sheet in cycle I (64.77%), it was included in the sufficient category and in cycle II, the teacher's ability continued to increase to (78.40%), namely in the good category, while in cycle III it continued to increase by ( 90.90%), namely in the very good category. The results of observations of student activity in cycle I (63.09%) were in the adequate category and in cycle II student activity increased (77.38%) included in the good category, cycle III it continued to increase by (89.28%)very good category. The results of students' understanding of concepts in cycle I with a percentage value (61.76%) included in the adequate category, in cycle II the average value had increased to (76.02%) including in the good category.cycle III it continued to increase by (87.64%), namely in the very good category and had fulfilled classical completeness